Association of foods enriched in conjugated linoleic acid (CLA) and CLA supplements with lipid profile in human studies: a systematic review and meta-analysis. Issue 11 (7th November 2014) - Derakhshande-Rishehri, Seyede-Masome; Mansourian, Marjan; Kelishadi, Roya; Heidari-Beni, Motahar
Abstract: Objective: The present study aimed to review the association of conjugated linoleic acid (CLA) consumption in two forms, foods enriched in CLA and CLA supplements, with serum lipid profile in human studies. Design: Systematic review and meta-analysis. Setting: Search process was conducted in PubMed, Cochrane Library, Google Scholar, Scopus and Science Direct. Clinical trials that investigated the association of CLA intakes either in the form of supplements or enriched foods with lipid profile in healthy adults were included. All outcomes were recorded as continuous variables, and the effect size was measured by analysis of the mean and standard deviation before and after the intervention for case and control groups. Subjects: Healthy adult population. Results: CLA supplementation was associated with a significant decrease in LDL cholesterol (mean difference=−0·218; 95 % CI −0·358, −0·077; P =0·002), a non-significant decrease in HDL cholesterol (mean difference=−0·051; 95 % CI −0·188, 0·086; P =0·468), a non-significant increase in total cholesterol (mean difference=0·009; 95 % CI −0·128, 0·146; P =0·896) and a non-significant decrease in TAG (mean difference=−0·065; 95 % CI −0·20, 0·07; P =0·344). Foods enriched with CLA were associated with significantly decreased LDL cholesterol (mean difference=−0·231; 95 % CI −0·438, −0·024; P =0·028), non-significantly increased HDL-C (mean difference=0·075; 95 % CI −0·121, 0·270; P =0·455), non-significantly decreased total cholesterol (mean difference=−0·158; 95 % CI −0·349, 0·042; P =0·124) and non-significantly decreased TAG (mean difference=−0·078; 95 % CI −0·274, 0·117; P =0·433). Conclusions: According to our analysis, consumption of foods enriched with CLA or CLA supplements has favourable effects on LDL cholesterol levels.